Effect of periodontal disease on children with diabetes and their quality of life - Aljohani, Hanan R.; Almazyad, Abdulsalam M.; Asiri, Atheer M.; Aref, Rana H.; Dweesh, Naief A. A. L.; Asiri, Abeer H.; Aljami, Nouf N.; Alzahrani, Mamdouh A.; Assiri, Mohammad Y.; Kemawi, Abdalmohsen A.; Moussa, Wiaam I. (International Journal Of Community Medicine And Public Health, 2022)
Diabetes mellitus (DM) is a life-altering and comparatively prevalent chronic condition affecting children. The root cause of the condition is linked to the pancreatic islets of Langerhans, which produce the hormone insulin and are destroyed by an autoimmune inflammation. The illness then shows up clinically as a result. In the context of the combination of hereditary and external variables, the condition emerges in people with polygenic genetic susceptibility. Concerning a potential connection involving DM and periodontitis, many investigations have been released. Conflicting results, though, have been recorded. Certain authors believe that individuals with DM have significantly higher levels of gingival inflammation and marginal periodontitis than non-DM controls, despite the fact that this association has not been discovered in another research. Dental plaque microbes are the primary cause of periodontal pathologies, in which the tissues around the teeth become infected. Periodontitis manifests in DM patients earlier than it does in the general demographic of healthy individuals. Periodontal deterioration typically shows up in children with DM throughout puberty, while it can happen sooner. Also, in juvenile subjects with type 1 DM, the development of periodontal infection has been linked to poorly managed DM. Elevated access to glucose in both the fluid around the gingival crevice and saliva promotes the growth of caries and periodontal pathology causing microbes and worsens oral inflammation. Owing to inflammation, periodontal disease affects the cellular and humoral immune systems. The generation of insulin and metabolic control are impacted by these modifications in immune responses. Thus, periodontal disease can hinder glycemic control, and impaired metabolic control can further encourage periodontitis; a loop may be generated that worsens both problems. Hence, it is vital to prevent and manage oral inflammatory conditions in order to effectively prevent and control DM complications.